Candidate Bioinks for Extrusion 3D Bioprinting—A Systematic Review of the Literature - Tarassoli, Sam P.; Jessop, Zita M.; Jovic, Thomas; Hawkins, Karl; Whitaker, Iain S. (Frontiers in Bioengineering and Biotechnology, 2021)
Purpose Our aim was to identify biomaterials that have been found to be suitable for extrusion 3D bioprinting, outline their biomechanical properties and biocompatibility towards their application for bioprinting specific tissue types. This systematic review provides an in depth overview of current biomaterials suitable for extrusion to aid bioink selection for specific research purposes and facilitate design of novel tailored bioinks. Methods A systematic search was performed on EMBASE, PubMed, Scopus and Web of Science databases according to the PRISMA guidelines. References of relevant articles, between December 2006 to January 2018, on candidate bioinks used in extrusion 3D bioprinting were reviewed by two independent investigators against standardised inclusion and exclusion criteria. Data was extracted on bioprinter brand and model, printing technique and specifications (speed and resolution), bioink material and class of mechanical assessment, cell type, viability and target tissue. Also noted were authors, study design (in vitro/in vivo), study duration and year of publication. Results A total of 9720 studies were identified, 123 of which met inclusion criteria, with 58 reports using natural biomaterials, 26 using synthetic biomaterials and 39 using a combination of biomaterials. Alginate (n=50) and PCL (n=33) were the most commonly used bioinks, Pneumatic extrusion bioprinting techniques were the most common (n=78), followed by piston (n=28). The majority of studies focus on the target tissue, most commonly bone and cartilage, and investigate only one bioink rather than assessing a range to identify those with the most promising printability and biocompatibility characteristics. The Bioscaffolder (GeSiM, Germany), 3D Discovery (regenHU, Switzerland) and Bioplotter (EnvisionTEC, Germany) were the most commonly used commercial bioprinters (n = 35 in total Many studies also failed to specify whether the mechanical data reflected pre-, during or post-printing, pre- or post-crosslinking and with or without cells Conclusions Despite the increase in the variety of biocompatible synthetic materials available, there has been a shift towards using natural rather than synthetic bioinks for extrusion bioprinting, dominated by alginate either alone or in combination with other biomaterials. Further research is needed on side by side characterisation of bioinks with standardisation of the type and timing of biomechanical assessment.